Study of Hantavirus Seroprevalence and Parasites from Rodents at Selected Residential Areas in Kuching and Betong Division - Ng, Yee Ling (Universiti Malaysia Sarawak (UNIMAS), 2015)
Rodents serves as the zoonotic reservoirs of numerous pathogens such as Hantavirus. Similarly, ectoparasites in rodents also act as arthropod vectors in the transmission of parasitic diseases. Therefore this study was done to determine the seroprevalence of Hantavirus and compare the species diversity of ectoparasites in rodent populations. A total of 44 rodents consisting three species (Rattus rattus, R. tiomanicus and Sundam)s muelleri) were trapped from four selected residential areas (Kampung Krusen Kranji, Serian; Kampung Sebayor, Kota Samarahan; Kampung Ulu Serian, Betong; and Kampung Bako Hulu, Kuching). Rattus ratter was the predominant rodent species with the highest prevalence of 79.55% (n=35), followed by S. muelleri (11.36%; n=5) and R. tiomanicus (9.09%; n=4). Hantavirus seroprevalence test was done on 28 selected rodent serum samples using ELISA kit but there was no seropositive samples detected. A total of 107 individuals of ectoparasites comprising three hard ticks species (Ixodes granulatus, Haemaphysalis sp. 1, Haemaphysalis sp. 2), three mesostigmatid mites species (Laelaps echidninus, L. sedlaceki, L. nuttalli), one chigger mites species (Chiggers sp. 1), and one lice species (Hoplopleura sp. ), were recovered from 32 out of 44 rodents (72.73%). L. echidninus was the generalist ectoparasite species which was found in all rodent species (65.91 %, n=29). Through diversity t-test, Kampung Ulu Serian and Kampung Sebayor showed a significantly higher species diversity compared to Kampung Krusen Kranji and Kampung Bako Hulu. For endoparasite detection, 26 of 44 trapped rodents (59.09%) were infected with nematodes while 17 (38.64%) were infected with cestodes. This data provide a useful database for Hantavirus surveillance in Malaysia, as well as to estimate parasitic disease outbreak for future studies.